An uncommon cause of acute abdomen - epiploic appendagitis: CT findings - Nihal USLU TUTAR; Esra ÖZGÜL; Dilek OĞUZ; Banu ÇAKIR; N. Çağla TARHAN; Mehmet COŞKUN (Turkish Journal of Gastroenterology, 2019)
-